Controlled fabrication, characterization and comparison of porous poly(l-lactide) and poly(d-lactide) films by electric breath figure. Issue 37 (29th March 2016) - Wang, Min-Yan; Wang, Han; Zhai, Song; Shen, Qing
Abstract : Porous poly(l -lactide), PLLA, and poly(d -lactide), PDLA, films were fabricated by the electric breath figure (EBF) method. Abstract : Porous poly(l -lactide), PLLA, and poly(d -lactide), PDLA, films were fabricated by the electric breath figure (EBF) method. The pore sizes of both the PLLA and PDLA films were reduced with the increase in electric voltage; however, the former followed a non-linear fit, whereas the latter followed a linear fit. Under 0 V condition, the average diameter, d a, was 15.0 ± 0.50 μm for the PLLA film and 6.66 ± 0.54 μm for the PDLA film, whereas under 3 kV condition, d a was 1.65 ± 0.35 μm for the PLLA film and 0.73 ± 0.07 μm for the PDLA film. FTIR spectra analysis showed that the EBF process did not change the structure of PLLA or PDLA.